2018
DOI: 10.1155/2018/4891418
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Electroplating Sludge as Subgrade Backfill Materials: Mechanical and Environmental Risk Evaluation

Abstract: The electroplating sludge may pose serious threat to human health and surrounding environment without safe treatment. This paper investigated the feasibility of using electroplating sludge as subgrade backfill materials, by evaluating the mechanical properties and environmental risk of the cement-coal fly ash solidified sludge. In this study, Portland cement and coal fly ash are used to solidify/stabilize the sludge. After curing for 7, 14, and 28 days, the stabilization/solidification sludge specimens were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Xia et al (2019) also observed the loss of resistance of products from S/S of lead-zinc smelting slag in composite-based geopolymer by increasing water contents, for a liquid to binder ratio higher than 0.20. Zhang et al (2018b) reported a decrease of 87.1% on compressive strength by increasing water content from 0 to 10%, when treating electroplating sludge with a mixture of coal fly ash and Portland cement.…”
Section: Paints Polymerisation Testmentioning
confidence: 99%
“…Xia et al (2019) also observed the loss of resistance of products from S/S of lead-zinc smelting slag in composite-based geopolymer by increasing water contents, for a liquid to binder ratio higher than 0.20. Zhang et al (2018b) reported a decrease of 87.1% on compressive strength by increasing water content from 0 to 10%, when treating electroplating sludge with a mixture of coal fly ash and Portland cement.…”
Section: Paints Polymerisation Testmentioning
confidence: 99%
“…The modern technologies development in Ukraine includes above all the use of the galvanic sludge as an inert filler in structural materials [7]. The sludge utilization as a sub-base material stabilized by cement and fly ash is solved in [8]. At the Northeast Normal University, China, the galvanic sludge re-use for a preparation of new adsorbents for waste water treatment has been brought into focus [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Cr/Ni electroplating sludge (ES), produced from the galvanizing of metallic surfaces to avoid corrosion, contains a relatively high amount of heavy metals (such as nickel, copper and chromium), soluble salts (chlorides and sulphates), pathogenic microorganisms and organic pollutants [1]. Thus, this Cr/Ni sludge has a serious biological toxicity and can be a threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, the amount of ES generated in the European Union (EU27) was around 150,000 tons [4]. The inertisation of the hazardous species of the ES in other processes/products might be a solution for avoiding the high costs associated with landfilling [1,5,6]. In this regard, the scientific community has been working on industrial waste valorisation to make processes more sustainable and efficient in relation to both economic and environmental aspects and contribute, in this way, to the circular economy.…”
Section: Introductionmentioning
confidence: 99%